Pulmonary Hypertension - Elwing, Jean M.; Panos, Ralph J. (IntechOpen, 2013)
This volume presents overviews as well as in depth reviews of many aspects of the clinical presentation, pathophysiology, and treatment of Pulmonary Hypertension (PH) especially PH related to thromboembolic disease. Saleem Sharieff presents a comprehensive synopsis of the epidemiologic, clinical, histopathologic, and therapy of PAH. Next, Dimitar Sajkov, Bliegh Mupunga, Jeffrey J. Bowden, and Nikolai Petrovsky comprehensively review World Health Organization group III PH. The cellular and biochemical pathophysiology of PH are summarized by Rajamma Mathew. Specific mechanisms implicated in the pathogenesis of PH are presented by Junko Maruyama, Ayumu Yokochi, Erquan Zhang, Hirohumi Sawada, Kazuo Maruyama; and Aureliano Hernandez and Rafael A. Areiza. Jean Elwing and Ralph Panos discuss PH associated with acute thromboembolism. Mehdi Badidi and M Barek Naz discuss PH caused by chronic thromboembolic disease. Juan C. Grignola, Maria J. Ruiz-Cano, Juan P. Salisbury, Gabriela Pascal, Pablo Curbelo, and Pilar Escribano present the physiologic assessment of patients with chronic thromboembolic disease prior to surgical pulmonary endarterectomy and, finally, Henry Liu, Philip L. Kalarickal, Yiru Tong, Daisuke Inui, Michael J Yarborough, Kavitha A. Mathew, Amanda Gelineau, and Charles Fox comprehensively review the clinical perioperative evaluation and management of patients with PH due to chronic thromboembolic disease.